Lola planta un jardín = Lola plants a garden - McQuinn, Anna; Beardshaw, Rosalind; Calvo, Carlos E.; McQuinn, Anna.; McQuinn, Anna. (Watertown, MA : Charlesbridge, 2017)
Lola plants a flower garden with her parent's help, and watches it grow.
"First published in the United Kingdom in 2014 by Alanna Books."
Translated by Carlos E. Calvo.
Text in English and Spanish.
Keywords: Flower gardening -- Juvenile fiction; African American girls -- Juvenile fiction; African American families -- Juvenile fiction; Flowers -- Fiction; Gardening -- Fiction; African Americans -- Fiction; Family life -- Fiction; Spanish language materials -- Bilingual